Reproductive Organ Education for Psychic Health Development of Early Age - Darwati, Dwi (International Conference of Moslem Society, 2018)
Reproductive health education should be given since early childhood by using language that is adapted to the stage of development. If you procrastinate and wait until the teenager it is already too late because in the days of the digital era, as now, all the information can be easily accessed by anyone including children early age. If the early childhood misinformed about their reproductive organs it would disrupt the physical and psychological development due to the wrong behavior in caring for and maintaining reproductive organs. Qur’an as the holy book of Muslims describes the steps of reproduction and imparting education wisely as well as how to apply such education. This kind of education must be in accordance with the conditions of children and there should not be a lie about it We can also use media and methods such as pictures, songs, tap or other visual media which can give clearer information, so that children can clearly see parts of the body, their characteristics, and how to treat and care them. The impropriate approach in conveying this kind of knowledge will be very dangerous for children. The provision of early age reproductive organs education can prevent the occurrence of deviant behavior as well as protect children from dangerous influence in early childhood development.